Thyroid skeletal metastasis: pain management with verteblation. Issue 1 (19th April 2017) - Orgera, Gianluigi; Krokidis, Miltiadis; Rebonato, Alberto; Tipaldi, Marcello Andrea; Mascagni, Luca; Rossi, Michele
Abstract : The combination of percutaneous vertebroplasty with radiofrequency ablation (verteblation) has not shown to be an effective measure of pain management in patients with metastatic lesions of the spine. The use of this novel technique has not been previously described in metastatic disease from thyroid cancer. We would like to report our experience after treating a patient affected by a thyroid carcinoma and an osteolytic spine metastasis. The patient suffered from life-limiting pain and was successfully treated with a combination of vertebroplasty and radiofrequency ablation. This case shows that the indications of verteblation may be expanded in the palliative treatment of metastatic disease from thyroid carcinoma.